2019
DOI: 10.5578/ced.201937
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Immunization Approaches of Caregivers: An Example of a Teaching and Research Hospital

Abstract: Çocuk aşılama programları sonucunda sağlık alanında ölümcül veya kalıcı sakatlıklar ile sonuçlanabilecek birçok hastalıklara karşı korunma sağlanmaktadır. Aşılama programlarında teknik altyapı ve personel en önemli kriter olsa da bakım verenlerin aşı programlarına uyumu önemi artan bir durum haline gelmiştir.Çalışmamızda ebeveynlerin aşı yaklaşımlarını etkileyen faktörleri belirlemek ve aşı isimlerini bilme düzeylerini saptamak amaçlanmıştır. Gereç ve Yöntemler: Bu kesitsel-tanımlayıcı çalışmada hastanemiz çoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
(21 reference statements)
4
9
0
Order By: Relevance
“…Eighty-eight point five percent of the mothers in the study stated that vaccines had side effects, and this rate was found to be 73.7% in another study [9]. In studies involving parents and adults, the rate of those who stated that vaccines had side effects was 53.6% and 67.7%, respectively [7,13]. In our study, it was determined that working mothers knew the side effects of vaccines with a higher frequency.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Eighty-eight point five percent of the mothers in the study stated that vaccines had side effects, and this rate was found to be 73.7% in another study [9]. In studies involving parents and adults, the rate of those who stated that vaccines had side effects was 53.6% and 67.7%, respectively [7,13]. In our study, it was determined that working mothers knew the side effects of vaccines with a higher frequency.…”
Section: Discussionmentioning
confidence: 56%
“…As a limitation of the study, working mothers constituted approximately one-fifth of the participants in this study. However, the participation of working mothers in similar studies was also low [7,9]. Different study designs in which the two groups show a similar distribution are needed to determine the factors affecting knowledge levels of working and…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary goal of health services and staff is to ensure that individuals continue to lead healthy lives. Vaccination is the most effective method of providing protection from infectious diseases [3]. Healthcare professionals who follow scientific innovations and whose knowledge is most sought after to protect public health serve as ambassadors of evidence-based medical interventions and are critical in promoting the adoption of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is the most effective method of providing protection from infectious diseases. Although technical infrastructure and healthcare workers are the most important criteria in vaccination studies, it has become important that healthcare providers have sufficient knowledge about vaccines and are informed about the necessity of vaccination through in-service training provided by the Ministry of Health [3].…”
Section: Introductionmentioning
confidence: 99%